2014
DOI: 10.1093/gbe/evu185
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfers Shaped the Evolution of De Novo NAD + Biosynthesis in Eukaryotes

Abstract: NAD+ is an essential molecule for life, present in each living cell. It can function as an electron carrier or cofactor in redox biochemistry and energetics, and serves as substrate to generate the secondary messenger cyclic ADP ribose and nicotinic acid adenine dinucleotide phosphate. Although de novo NAD+ biosynthesis is essential, different metabolic pathways exist in different eukaryotic clades. The kynurenine pathway starting with tryptophan was most likely present in the last common ancestor of all eukar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 80 publications
(117 reference statements)
4
22
0
Order By: Relevance
“…linking TCA and ETC), we investigated its de novo synthesis mechanisms (Figure 4). As expected, all Asgardaeota phyla were found to harbor the aspartate pathway 19 - a set of metabolic transformations that can occur in both presence or absence of oxygen 20 , and which are characteristic for most prokaryotes and the plastid-bearing eukaryotes (obtained through lateral gene transfer from their cyanobacterial endosymbiont) 18 . Surprisingly, Heimdallarchaeia presented in addition to the aspartate pathway the exclusively aerobic kynurenine one 21 (Figure 4), which is reported to be present in few bacterial groups and eukaryotes 18 .…”
Section: Mainsupporting
confidence: 57%
See 3 more Smart Citations
“…linking TCA and ETC), we investigated its de novo synthesis mechanisms (Figure 4). As expected, all Asgardaeota phyla were found to harbor the aspartate pathway 19 - a set of metabolic transformations that can occur in both presence or absence of oxygen 20 , and which are characteristic for most prokaryotes and the plastid-bearing eukaryotes (obtained through lateral gene transfer from their cyanobacterial endosymbiont) 18 . Surprisingly, Heimdallarchaeia presented in addition to the aspartate pathway the exclusively aerobic kynurenine one 21 (Figure 4), which is reported to be present in few bacterial groups and eukaryotes 18 .…”
Section: Mainsupporting
confidence: 57%
“…As expected, all Asgardaeota phyla were found to harbor the aspartate pathway 19 - a set of metabolic transformations that can occur in both presence or absence of oxygen 20 , and which are characteristic for most prokaryotes and the plastid-bearing eukaryotes (obtained through lateral gene transfer from their cyanobacterial endosymbiont) 18 . Surprisingly, Heimdallarchaeia presented in addition to the aspartate pathway the exclusively aerobic kynurenine one 21 (Figure 4), which is reported to be present in few bacterial groups and eukaryotes 18 . The phylogenetic reconstruction and evolutionary history inferences showed that this pathway, which is considered to be present in the protoeukaryote ancestor 18 , was probably acquired by Heimdallarchaeia through lateral gene transfer from bacteria (Supplementary Figure S3).…”
Section: Mainsupporting
confidence: 57%
See 2 more Smart Citations
“…NAD + has central roles in a variety of biological processes ranging from cellular metabolism and energy production to the regulation of enzymatic activities. 14 Accumulating evidence reveals that NAD + serves as a substrate for non-redox reactions, which are essential for diverse biological functions such as gene expression, Ca 2+ mobilization and cell death. Importantly, as mentioned above, NAD + serves as a key cofactor of SIRTs in removing the acetyl moiety from various proteins, and hence has a crucial role in regulating their activities.…”
mentioning
confidence: 99%